ANALISIS PERAN GURU DALAM MENGELOLA HASIL BELAJAR SISWA DI SDN 8 DUNGALIYO, GORONTALO - Yusuf, Chairil Anaz; Pomalingo, Samsi; Nurainun, Nurainun (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to analyses the role of teachers in managing student learning outcomes at SDN 8 Dungaliyo, Gorontalo. Using a qualitative and phenomenological approach, data were collected through participant observation, in-depth interviews, and documentation. The results indicate that a variety of teaching methods, such as lectures, discussions, and demonstrations, significantly contribute to the improvement of student learning outcomes. The use of formative and summative assessments helps teachers provide constructive feedback to enhance students' understanding. Furthermore, effective classroom management and a positive learning environment increase student engagement. Parental involvement and the utilization of technology also prove to be important in supporting the learning process. This study concludes that collaboration among teachers and a differentiated approach in identifying students' learning needs can enhance the quality of education. However, the challenges of managing diverse student abilities require special attention from educators to ensure that each student can achieve their maximum potential.